Notice of Retraction Monitoring and Controlling of Industrial Crane using Programmable Logic Controllers - Harpreet Singh Bedi; Krishan Arora (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
Notice of Retraction-----------------------------------------------------------------------After careful and considered review of the content of this paper by a duly constituted expert committee, this paper has been found to be in violation of IAES's Publication Principles.We hereby retract the content of this paper. Reasonable effort should be made to remove all past references to this paper.The presenting author of this paper has the option to appeal this decision by contacting ijeei.iaes@gmail.com.-----------------------------------------------------------------------In this paper, we will work on Programmable logic Controllers to control the operation of An Industrial Crane and many other Applications which is used in the industry. Earlier in Industry, We used certain control devices which were controlled and wired directly with the system that leads to certain irregularity in the functioning of the whole system. To overcome the in-functionality of the system which was caused by large number of wires, We came cross towards Programmable logic controllers (PLC).Earlier Human controls the crane & that passes through large drawbacks such as more wiring work, appears large mechanical faults & difficulties in troubleshooting & repair work .Due to these Drawbacks the production suffers a lot and hence growth decreases rapidly.